Alteration of structure and function of ATP synthase and cytochrome c oxidase by lack of Fo-a and Cox3 subunits caused by mitochondrial DNA 9205delTA mutation - Hejzlarová, Kateřina; Kaplanová, Vilma; Nůsková, Hana; Kovářová, Nikola; Ješina, Pavel; Drahota, Zdeněk; Mráček, Tomáš; Seneca, Sara; Houštěk, Josef (The Biochemical journal, 2015)
Mutations in the MT-ATP6 gene are frequent causes of severe mitochondrial disorders. Typically, these are missense mutations, but another type is represented by the 9205delTA microdeletion, which removes the stop codon of the MT-ATP6 gene and affects the cleavage site in the MT-ATP8/MT-ATP6/MT-CO3 polycistronic transcript. This interferes with the processing of mRNAs for the Atp6 (Fo-a) subunit of ATP synthase and the Cox3 subunit of cytochrome c oxidase (COX). Two cases described so far presented with strikingly different clinical phenotypes-mild transient lactic acidosis or fatal encephalopathy. To gain more insight into the pathogenic mechanism, we prepared 9205delTA cybrids with mutation load ranging between 52 and 99% and investigated changes in the structure and function of ATP synthase and the COX. We found that 9205delTA mutation strongly reduces the levels of both Fo-a and Cox3 proteins. Lack of Fo-a alters the structure but not the content of ATP synthase, which assembles into a labile, ∼60 kDa smaller, complex retaining ATP hydrolytic activity but which is unable to synthesize ATP. In contrast, lack of Cox3 limits the biosynthesis of COX but does not alter the structure of the enzyme. Consequently, the diminished mitochondrial content of COX and non-functional ATP synthase prevent most mitochondrial ATP production. The biochemical effects caused by the 9205delTA microdeletion displayed a pronounced threshold effect above ∼90% mutation heteroplasmy. We observed a linear relationship between the decrease in subunit Fo-a or Cox3 content and the functional presentation of the defect. Therefore we conclude that the threshold effect originated from a gene-protein level.
Keywords: buněčné linie; DNA, Mitochondrial; mutace; Electron Transport Complex IV; delece genu; Gene Deletion; Humans; Cell Line; respirační komplex IV; Mitochondrial Proton-Translocating ATPases; lidé; Mutation; Protein Subunits; podjednotky proteinů; mitochondriální DNA; mitochondriální protonové ATPasy